Effect of gamma-ray irradiated reduced graphene oxide (rGO) on environmental health: An in-vitro and in-vivo studies. (1st February 2023) - Sivaselvam, S.; Mohankumar, A.; Narmadha, R.; Selvakumar, R.; Sundararaj, P.; Viswanathan, C.; Ponpandian, N.
Abstract: The unique properties of reduced graphene oxide (rGO) have drawn the attention of scientists worldwide since the last decade and it is explored for a wide range of applications. However, the rapid expansion of rGO use in various products will eventually lead to environenal exposure and rises a safety concern  on the environment and humal health risk. Moreover, the utilization of toxic chemicals for the reduction of graphene oxide (GO) into rGO is not environmentally friendly, warranting the exploration of non-toxic approaches. In the present work, rGO was synthesized using a different dose of gamma-ray irradiation and characterized. The in-vitro and in-vivo analysis indicated that the gamma-irradiated rGO induced toxicity depending on its degree of reduction and dosage. In the L929 cells, rGO-30 KGy significantly induced cytotoxicity even at low concentration (1 mg L −1 ) by inducing reactive oxygen species (ROS), lactate dehydrogenase (LDH) enzyme production, nuclear fragmentation and apoptosis. The change in morphology of the cells like membrane blebbing and cell rounding was also observed via FESEM. In the in-vivo model Caenorhabditis elegans, rGO-30 KGy significantly affected the functioning of primary and secondary targeted organs and also negatively influenced the nuclear accumulation of transcription factors (DAF-16/FOXO and SKN-1/Nrf2), neuronal health, and antioxidant defense mechanism of the nematodes. The real-time PCR analysis showed significant up-regulation ( ced-3, ced-4, cep-1, egl-1, and hus-1 ) and down-regulation ( ced-9 ) of the gene involved in germ-line and DNA damage-induced apoptosis. The detailed toxicity mechanism of gamma irradiated rGO has been elucidated. This work highlights the toxicity of rGO prepared by gamma-ray radiation and paves way for understating the toxicity mechanism. Graphical abstract: Image 1 Highlights: Increased use of rGO leads to environment exposure and concerns human health. rGO-30 KGy induce nuclear fragmentation and apoptosis in L929 cells. Environmental toxicity of gamma irradiated rGO was first reported in C. elegans . Radical generation and oxidative potential of rGO-30 KGy induce higher toxicity. rGO induces apoptosis, ROS and declines neuronal development in C. elegans .